The interaction of an oscillating airfoil and/or flap with a separating flow - Lang, James D. (Cranfield University, 1975)
At present little is known of the dynamics of a separating and reattaching flowfield. This unsteady flow topic relates to a wide range of aerodynamic problems such as dynamic stall and contfol-sürface-buzz. An experiment was performed with the purpose of investigating the dynamics of a separated region and the effect of the region on the motion of a flap-type control surface. A NACA 0012 airfoil section was fitted with a movable spoiler and flap. Measurements were made of the unsteady, non-linear hinge-moment due to spoiler oscillation. Aerodynamic hinge-moment was also investigated with the spoiler fixed and the flap oscillated harmonically. Flap response to spoiler-induced forcing was also observed in addition to observations of coupled spoiler and flap system behavior. The coupled system exhibited limit-eyele oscillations. Flap response to spoiler-induced loading can be predicted well by use of a linear equation for flap motion which is forced by the effect of spoiler motion. The equation of motion includes attached flow values of aerodynamic damping and stiffness. A theory is developed which models separation bubble dynamics. It includes a quasi-steady model for the external shear-layer, and flow of mass within the bubble at a mean reversed-flow velocity. Pressure perturbations along the bubble are modeled also. The theory is used with the method of Beecham and Titchener in order to predict limit-cycle behavior of the coupled system. Good agreement with experimental results is achieved. The instant of instability and of growth of a laminar separation bubble at the leading-edge of an oscillating airfoil is also investigated theoretically. The beginning of dynamic stall is seen to be related to the dynamics of a separation bubble and the inviscid flowfield. The theory is applied also to a study of the phenomena of control-surface-buzz, where separation is induced by shock waves.